Preparing for Pregnancy in Women with Systemic Lupus Erythematosus—A Multidisciplinary Approach - Ioana Cristina Saulescu; Daniela Opris-Belinski; Andra Rodica Balanescu; Bogdan Pavel; Nicolae Gica; Anca Maria Panaitescu (Medicina, 2022)
Pregnancy is one of the most challenging processes the human body is exposed to: the healthy mother can carry to term a genetically different new-born, while her immune system adapts to tolerate this new status and avoids rejection. In autoimmune disorders, motherhood is even more challenging, with additional medical counselling, mother care, and foetus development checks being necessary. While the aspects of supplementary mother care and pregnancy progress tracking are associated with well-established medical procedures and protocols, counselling, be it pre- or post-conception, is still underestimated and scarcely applied. Indeed, over the past decades, medical counselling for this particular population has changed significantly, but from a healthcare’s provider point of view, more is required to ensure a smooth, controllable pregnancy evolution. One of the most frequent autoimmune diseases affecting young females during their fertile years is Systemic Lupus Erythematosus (SLE). Like other heterogenous diseases, it exposes the mother to severe, organ-threatening complications and unpredictable evolution. Both the disease and its treatment can significantly affect the mother’s willingness to engage in a potentially risky pregnancy, as well as the likeliness to carry it to term without any impairments. A good collaboration between the patient’s rheumatologist and obstetrician is therefore mandatory in order to: (a) allow the mother to make an informed decision on pursuing with the pregnancy; (b) ensure a perfect synchronization between pregnancy terms and treatment; and (c) avoid or minimize potential complications. The best approach to achieve these outcomes is pregnancy planning. Moreover, knowing one desired prerequisite for a successful pregnancy evolution in SLE mothers is a stable, inactive, quiescent disease for at least six months prior to conception, planning becomes more than a recommended procedure. One particular aspect that requires attention before conception is the treatment scheme applied before delivery as autoantibodies can influence significantly the course of pregnancy. In this view, future SLE mothers should ideally benefit from preconception counselling within their agreed care pathway. A multidisciplinary team including at least the rheumatologist and obstetrician should be employed throughout the pregnancy, to decide on the appropriate timing of conception and compatible medication with respect to disease activity, as well as to monitor organ involvement and foetus development progress.